Molecular basis underpinning MR1 allomorph recognition by an MR1-restricted T cell receptor - Richard J. Suckling; Cevriye Pamukcu; Robert Alan Simmons; Daniel Fonseca; Emma Grant; Rory Harrison; Saher A. Shaikh; Rahul C. Khanolkar; Hemza Ghadbane; Andrew Creese; Miriam Hock; Thomas G. Gligoris; et al. (Frontiers in Immunology)
IntroductionThe MHC-class-I-related molecule MR1 presents small metabolites of microbial and self-origin to T cells bearing semi-invariant or variant T cell receptors. One such T cell receptor, MC.7.G5, was previously shown to confer broad MR1-restricted reactivity to tumor cells but not normal cells, sparking interest in the development of non-MHC-restricted immunotherapy approaches.Methods/ResultsHere we provide cellular, biophysical, and crystallographic evidence that the MC.7.G5 TCR does not have pan-cancer specificity but is restricted to a rare allomorph of MR1, bearing the R9H mutation.DiscussionOur results underscore the importance of in-depth characterization of MR1-reactive TCRs against targets expressing the full repertoire of MR1 allomorphs.